QUICK MASSAGE IN UNIVERSITY TEACHERS FOR STRESS REDUCTION (Fiep Bulletin - online, 2019)
INTRODUCTION: The Quick Massage technique consists of manipulating the main tension points such as neck,back, arms and shoulders, providing relaxation of the body, immediate tension relief, physical and mental fatigue, musclediscomfort, tendonitis, headaches, improvement of the blood circulation and reactivation of the energy lost during the day, beingable to reduce the stress with application of 15 minutes of massage. PURPOSE: to apply Quick massage to university teachersfor stress reduction. METHODOLOGY: The application of Quick Massage to university teachers, 53 volunteers of both sexes,between 27 and 68 years old, in two sessions, at the Anhembi Morumbi University Campus - Campus Centro. Procedure wasperformed through the volunteer reception, filling in the technical file, blood pressure measurement, after being referred to theQuick Massage with duration of 15 minutes. At the end of the massage, blood pressure was again measured. The sampleconsisted of 53 teachers. RESULTS: From this sample it was possible to attend teachers from 26 different areas of activity and itwas found that 38 of the 53 teachers had their blood pressure reduced. All volunteer participants reported relief of muscletensions, body relaxation, increased sense of physical and mental disposition. FINAL CONSIDERATIONS: We conclude that theQuick massage technique is indicated for the reduction of stress and promotes physical and mental well-being.
Keywords: Quick Massage; Teachers; Stress